Learning Achievement and Satisfaction in Online versus Face-to-Face Mathematics Classes: Primary Education in Bangladesh Perspective (Journal of Primary Education, 2022)
Both online and offline classroom environments, there are inequalities between academic performance and sanctification. The purpose of the study was to examine the extent to which online learning influence students’ academic achievement as compared to face-to-face mode in the context of primary education in Bangladesh. This study followed an explanatory mixed-method design where quantitative data was obtained by quasi-experimental design and qualitative data by semi-structured interviews. 12 teachers and 40 students of Grade- IV from JAAGO Foundation Online school of Bangladesh were treated as samples of the study. The results of the two-tailed T-test illustrate traditional face-to-face classroom learning as the more effective and qualitative study demonstrated the satisfactory level of online mathematics learning as an average. Colorful learning materials, content visualization, animated shows about mathematics, video storytelling of practicing arithmetic in real life, and some shortcomings, such as communication gaps, lack of effective evaluation, feedback, topic knowledge, and plagiarism practice, were among the qualitative findings. This research illustrates which platforms assist students in improving their academic performance and increasing teachers’ satisfaction. However, students' satisfaction with online learning and how this satisfaction affects academic achievement could be the subject of future research.